Chirality-biased protein expression profile during early stages of bone regeneration - Zeng, Qiang; Zheng, Huimin; Heng, Boon Chin; Yao, Weitong; Yang, Yue; Jiang, Shengjie; Deng, Xuliang (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction: Chirality is a crucial mechanical cue within the extracellular matrix during tissue repair and regeneration. Despite its key roles in cell behavior and regeneration efficacy, our understanding of chirality-biased protein profile in vivo remains unclear. Methods: In this study, we characterized the proteomic profile of proteins extracted from bone defect areas implanted with left-handed and right-handed scaffold matrices during the early healing stage. We identified differentially-expressed proteins between the two groups and detected heterogenic characteristic signatures on day 3 and day 7 time points. Results: Proteomic analysis showed that left-handed chirality could upregulate cell adhesion-related and GTPase-related proteins on day 3 and day 7. Besides, interaction analysis and in vitro verification results indicated that the left-handed chiral scaffold material activated Rho GTPase and Akt1, ultimately leading to M2 polarization of macrophages. Discussion: In summary, our study thus improved understanding of the regenerative processes facilitated by chiral materials by characterizing the protein atlas in the context of bone defect repair and exploring the underlying molecular mechanisms of chirality-mediated polarization differences in macrophages.